![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(2.5^2.3^2+\left\{\left[2.5^3-\left(5x+4\right).5\right]:\left(2^2.3.5\right)\right\}=453\)
\(2.25.9+\left\{\left[2.125-\left(5x+4\right).5\right]:\left(4.3.5\right)\right\}=453\)
\(50.9+\left\{\left[250-\left(5x+4\right).5\right]:60\right\}=453\)
\(450+\left\{\left[250-\left(5x+4\right).5\right]:60\right\}=453\)
\(\left[250-\left(5x+4\right).5\right]:60=453-450\)
\(\left[250-\left(5x+4\right).5\right]:60=3\)
\(250-\left(5x+4\right).5=3.60\)
\(250-\left(5x+4\right).5=180\)
\(\left(5x+4\right).5=250-180\)
\(\left(5x+4\right).5=70\)
\(5x+4=70:5\)
\(5x+4=14\)
\(5x=14-4\)
\(5x=10\)
\(x=10:5\)
\(x=2\)
Vậy \(x=2\)
b) \(\left|x-\frac{1}{3}\right|=2\)
\(\Rightarrow\orbr{\begin{cases}x-\frac{1}{3}=-2\\x-\frac{1}{3}=2\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x=\left(-2\right)+\frac{1}{3}\\x=2+\frac{1}{3}\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x=\frac{-5}{3}\\x=\frac{7}{3}\end{cases}}\)
Vậy \(x\in\left\{\frac{-5}{7};\frac{7}{3}\right\}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
52x-3 - 2.52 = 52.3
52x-3 = 52.3 + 2.52
52x-3 = 52.(3 + 2)
52x-3 = 52.5 = 53
=> 2x - 3 = 3
=> 2x = 3 + 3
=> 2x = 6
=> x = 6 : 2
=> x = 3
Vậy x = 3
52x-3-2.52=52.3
52x-3-50=75
52x-3=125
52x-3 = 53
2x-3=3
2x=6
x=3
![](https://rs.olm.vn/images/avt/0.png?1311)
\(5^{2x-3}-2.5^2=5^2.3\)
\(5^{2x-3}-50=75\)
=>\(5^{2x-3}=75+50=125\)
Mà \(5^{2x-3}=125=5^3\)
=>2x-3=3
2x=3+3=6
=>x=3
-52x-32.52=52.3
\(5^{2x-3}\)-50=75
\(5^{2x-3}\)=75+50
\(5^{2x-3}\)=215
\(5^{2x-3}\) =\(5^3\)
\(\Rightarrow\) \(2x-3=3\)
\(2x=3+3\)
\(2x=6\)
\(x=6:2\)
\(x=3\)
Vậy x = 3
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
3^2x = 81
=> 3^2x = 3^4
=> 2x = 4
=> x = 2
5^x-3 - 2. 5^2 = 5^2. 3
=> 5^x-3 - 2 = 3
=> 5^x-3 = 5
=> x - 3 = 1
=> x = 4
![](https://rs.olm.vn/images/avt/0.png?1311)
a: \(\Leftrightarrow\left[\left(3x+14\right):4-3\right]:2=1\)
=>(3x+14):4-3=2
=>(3x+14):4=5
=>3x+14=20
=>3x=6
hay x=2
b: \(\Leftrightarrow\left[\left(x:4+17\right):10+3\cdot16\right]:10=5\)
\(\Leftrightarrow\left(x:4+17\right):10=50-48=2\)
=>x:4+17=20
=>x:4=3
hay x=12
c: \(\Leftrightarrow2\cdot15^2+\left[2\cdot125-\left(2x+4\right)\cdot5\right]:19=453\)
\(\Leftrightarrow250-\left(2x+4\right)\cdot5=\left(453-450\right)\cdot19=57\)
=>5(2x+4)=197
=>2x+4=197/5
=>2x=177/5
hay x=177/10
d: \(\Leftrightarrow\left(19x+50\right):14=5^2-4^2=9\)
=>19x+50=126
=>19x=76
hay x=4
e: \(\Leftrightarrow2\cdot3^x=10\cdot3^{12}+8\cdot3^{12}=18\cdot3^{12}\)
\(\Leftrightarrow3^x=3^2\cdot3^{12}=3^{14}\)
hay x=14
f: \(\Leftrightarrow3\left(x+2\right):7=30\)
=>3(x+2)=210
=>x+2=70
hay x=68
g: \(2480-1570+200-x+5=1010\)
=>1115-x=1010
hay x=105
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 5x = 125
\(\Rightarrow\)5x = 53
\(\Rightarrow\)x = 3
b, 32x = 81
\(\Rightarrow\)32x = 34
\(\Rightarrow\)2x = 4
\(\Rightarrow\) x = 4 : 2
\(\Rightarrow\) x = 2
c, 52x-3 - 2 . 52 = 52 . 3
52x-3 - 2 . 25 = 25 . 3
52x-3 - 50 = 75
52x-3 = 75 + 50
52x-3 = 125
52x-3 = 53
2x - 3 = 3
2x = 3 + 3
2x = 6
x = 6 : 2
x = 3
a, 5x = 125 suy ra 5x = 53 suy ra x = 3
b, 32x = 81 suy ra 32x = 34 suy ra x = 2
c, 52x - 3 - 2.52 = 52 . 3
suy ra 52x : 53 = 52 .3 + 2. 52
suy ra 52x : 53 = 52 . 5
suy ra 52x = 53 . 52 . 53
52x = 56 suy ra 2x = 6 suy ra x = 3
5^(2x-3) = 5^2 .3 +5^2 .2
5^(2x-3)=5^3
2x-3=3
2x=6
x=3